2014
DOI: 10.1002/2013gc005138
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence for the fractionation of carbon isotopes between diamond and iron carbide from the Earth's mantle

Abstract: We have studied two samples of mantle diamond containing iron carbide inclusions from Jagersfontein kimberlite, South Africa. Syngenetic crystal growth is inferred using morphological characteristics. These samples provide an opportunity to investigate the isotopic partitioning of 13 C in a terrestrial natural high-pressure and high-temperature (HPHT) system. The difference for the d 13 C values between the diamond and coexisting iron carbide averaged 7.2 6 1.3&. These data are consistent with available data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…This relationship is firm evidence for a subducted protolith and makes it extremely unlikely that the associated negative δ 13 C values are related to deep mantle isotopic fractionation (Mikhail et al, 2014). In a subduction scenario, the low δ 13 C values (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This relationship is firm evidence for a subducted protolith and makes it extremely unlikely that the associated negative δ 13 C values are related to deep mantle isotopic fractionation (Mikhail et al, 2014). In a subduction scenario, the low δ 13 C values (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, this interpretation is not unique. For example, Mikhail et al (2014) suggested that iron carbide inclusions in diamonds from Jagersfontein document isotopic fractionation (Δ 13 C carbide-diamond >7 ‰) sufficiently strong to cause the observed 13 C depleted signature. Similarly, evidence based on the rare earth element signatures (observation of negative Eu anomalies) of majoritic garnet inclusions from Jagersfontein, interpreted to reflect feldspar fractionation in crustal protoliths (Tappert et al, 2005b), was disputed by Griffin and O'Reilly (2007) and Corgne et al (2012) who considered Eu anomalies to reflect redoxrelated metasomatic signatures, or crystallisation from a melt at high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental studies of isotopic fractionations are limited to ~4 ‰ in between carbon species in closed systems at 1,000 °C (Bottinga 1969;Deines 1980). A recent study of isotopic fraction between iron carbide and diamond in natural samples observed a fractionation of 7.2 ‰ (Mikhail et al 2014a), however, in the wrong sense to explain light diamond formation from mantle material. Increasing temperature would reduce fractionation, and the effects of pressure remain mostly unconstrained.…”
Section: Subducted Source Of Isotopically Light Carbonmentioning
confidence: 99%
“…Very low δ 13 C values (−18‰ to −35‰) have been reported for SiC from several localities (25). Recently, Mikhail et al (8) C values, points to a genetic relationship between these diamonds with low δ…”
mentioning
confidence: 94%
“…In the presence of Fe-rich metals, diamond can be converted to iron carbides (Fe 3 C and Fe 7 C 3 ) and dissolved C in Fe−Ni metals (5-7). The occurrence of cohenite, (Fe, Ni) 3 C, has been well documented from iron meteorites, but only recently, several investigators reported rare terrestrial occurrences of Fe carbides (Fe 3 C, Fe 2 C, and Fe 23 C 6 ) from kimberlite (8), from minerals of subcratonic lithosphere or possible lower-mantle origins (9, 10) and others (11). Thus, Fe carbides and Fe−Ni metals are increasingly recognized as potential C-bearing phases in the lower mantle and core.…”
mentioning
confidence: 99%